The Implementation of Corporate Social Responsibility on Environmental Management and Its Effect on Local Community - Al Khotib, Muhammad; Nasution, Zulkifli; Alief Aththoric, T. (TALENTA Publisher, Universitas Sumatera Utara, 2024)
The role of companies as actors in production processes that utilize nature and resources is crucial. Therefore, to reduce increasing environmental degradation, companies carry out activities that are not only aimed at making profits but also pay more attention to survival, nature preservation, and socio-economic communities in the areas where they operate through corporate social responsibility (CSR). This research aims to evaluate the implementation of corporate social responsibility (CSR) programs and environmental management carried out by PT Sorik Marapi Geothermal Power (PT SMGP) and their impact on the local communities around the company's operational area. This evaluation includes the effectiveness and efficiency of the CSR programs implemented by PT SMGP, as well as the environmental management efforts undertaken. The data collection methods used are observation methods, interview methods, and documentation methods. The source of information in this research uses primary and secondary data. The research shows that, first, the company's CSR programs include relationship building, public services, and community empowerment. Second, environmental management activities carried out by the company are still not effective and efficient because many bad incidents occur, such as gas poisoning, noise, and drought.